(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
We, as women, are present in various spaces of knowledge production and it is no different in Puppet Theater. Here, we bring a part of our journey inside the Puppet Theater, focusing on the masks we experience, in order to touch curious hearts from the point of view of two artists-women-researchers. Here we investigate the materialities of this scenic object and, consequently, the impacts generated by them on stage. By researching the mask, its forms and how it reflects on the visual production, we can accurately observe the flowering of a thought, a dream, the imaginary.